Dark side of the shoulder: suprascapular and axillary nerve compressions - Ayik, Gokhan; Kolac, Ulas Can; Kaymakoglu, Mehmet; McFarland, Edward; Huri, Gazi (International orthopaedics, 2025)
Background The suprascapular and axillary nerves can be subject to entrapment due to both their anatomical courses and their anatomical relationships with surrounding anatomical structures around shoulder. These entrapments were previously considered as a diagnosis of exclusion. However, today these pathologies can be diagnosed as primary. The most common complaints of patients are pain and sometimes weakness. The clinician’s suspicion is very important in making diagnosis. The patient’s history, duration of symptoms, and information such as the movements in which the complaints increase should be questioned carefully and in detail. In physical examination, symmetrical evaluation of both shoulders can provide important information. In addition, cervical and brachial plexus pathologies should be kept in mind. According to the suprascapular and axillary nerve innervations, muscle atrophy should be evaluated during inspection. Range of motion and neurological examination around shoulder should be performed. Since these entrapments can be seen together with rotator cuff tears and labrum pathologies etc., these additional pathologies should also be targeted during evaluation. The evaluation should be expanded with imaging methods such as plain radiographs, ultrasonography, computed tomography, magnetic resonance imaging, electrodiagnostic studies and local anaesthetic injections to the entrapment area. There is no definitive method to diagnose these pathologies. As a result of all these evaluations, a diagnosis can be made. There is no consensus on treatment. In isolated entrapment cases where there are no additional surgical pathologies such as space-occupying lesions, non-operative treatment is primarily recommended. It is generally recommended to try non-operative treatment for at least six months. Surgical treatment is recommended in cases where non-operative treatment fails or in cases where there are additional pathologies requiring surgery or in cases where there is extrinsic compression such as sapce-occupying lesions. In the decision and choice of surgical treatment, it is very important to determine the aetiology precisely. Surgical treatment can be performed open and arthroscopically. Various additional arthroscopic portals and techniques have been described. However, there is no clear consensus on the superiority of these treatments over each other. Although physical therapy is recommended after surgical treatment, there is no consensus on this issue in the literature. Aim This review aims to summarize the diagnosis and management of suprascapular and axillary nerve entrapments in athletes, focusing on clinical presentation, diagnostic methods, treatment options, and current controversies.